A kind of impact-resistant high-hardness coating and preparation method and application

By using a composite structure of high-entropy alloy layer, pure binary alloy layer, gradient binary alloy layer and ternary or quaternary nitride layer in the hard coating, combined with vapor deposition technology, the hard coating is solved at high speed The peeling problem during hit achieves coating performance with high adhesion, high toughness and high hardness.

CN114107905BActive Publication Date: 2024-12-17GUANGZHOU GRANDTECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202111313781.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-08
Publication Date
2024-12-17
Estimated Expiration
2041-11-08

AI Technical Summary

Technical Problem

The existing hard coatings are inadequate in high-speed high-precision processing and sports equipment due to peeling problems, resulting in insufficient toughness and impact resistance. Especially when hitting at high speed, cracks are prone to occur, resulting in failure of the coating.

Method used

Using a composite coating structure composed of a high-entropy alloy layer, a pure binary alloy layer, a gradient binary alloy layer and a ternary or quaternary nitride layer, it is prepared by magnetron sputtering and cathode arc deposition technology, combined with vapor deposition Component modulation features, design a composite structure between the top ternary or quadrimer nitride layer and the bottom high-entropy alloy layer to increase interface adhesion and toughness, and add a binary alloy buffer layer in the middle to coordinate deformation differences.

Benefits of technology

The coating is achieved with high adhesion, high toughness, high strength and high hardness, effectively inhibiting the invasion and expansion of cracks, improving the overall performance of the coating, and preventing peeling during high-speed hits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114107905B_ABST
    Figure CN114107905B_ABST
Patent Text Reader

Abstract

The present invention discloses an impact-resistant high-hardness coating, a preparation method and an application thereof, and relates to the field of novel thin film materials. The coating comprises a high-entropy alloy layer, a binary alloy layer and a ternary or quaternary nitride layer, wherein the high-entropy alloy layer comprises a FeMnCrCo layer and / or (FeMnCrCo) 1‑x1 C x1 Gradient layer; binary alloy layer including TiAl layer or CrAl layer and (TiAl) 1‑x2 N x2 Gradient layer or (CrAl) 1‑x2 (CN) x2 Gradient layer; ternary or quaternary nitride layer is TiAlN layer, CrAlN layer, (CrAlSi) 1‑X3 N X3 Layer or (TiAlSi) 1‑X3 N X3 The high toughness of the coating interface of the present application can inhibit the initiation of cracks, and the binary alloy layer plays a buffering role, effectively inhibiting the expansion of cracks. At the same time, combined with the effect of the bottom layer, the coating as a whole achieves high toughness, high strength, high hardness, and anti-stripping properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of novel film materials, and in particular to an impact-resistant high-hardness coating and a preparation method and application thereof. Background Art

[0002] The application fields of hard coating are becoming more and more extensive. According to statistics, more than 85% of tools use hard coating, and 100% of them are used in the field of high-speed and high-precision machining. Hard coating is also widely used in the field of sports equipment to improve the texture and durability of the device. When the cutting tool is processed at high speed and intermittently, and sports equipment is hit hard, the peeling of the hard coating becomes its main failure mode. Therefore, under the premise of ensuring the high hardness and wear resistance of the coating, how to improve the toughness and impact resistance of the hard coating has become an urgent need in many application fields.

[0003] It is well known that when a coating is subjected to strong impact or blow, the initiation and expansion of cracks are the essential problems that lead to coating peeling. According to the theories of Hertz and others, the maximum tensile stress or shear stress during impact / blow occurs in the sub-surface layer and the surface at a certain distance from the striking point, which is the interface for most hard coatings. Therefore, high strength and high toughness of the interface are the key to inhibiting crack initiation, which is equally important as controlling crack expansion. Summary of the invention

[0004] The present invention provides an impact-resistant high-hardness coating and a preparation method and application thereof, so as to solve the technical problems of low strength and insufficient toughness of current alloy coatings, and provide a coating with high adhesion, high toughness, high strength and high hardness.

[0005] In order to solve the above technical problems, one of the purposes of the present invention is to provide an impact-resistant high-hardness coating, comprising a high-entropy alloy layer, a binary alloy layer and a ternary nitride layer or a quaternary nitride layer sequentially applied to a workpiece, wherein the high-entropy alloy layer comprises a FeMnCrCo layer and / or (FeMnCrCo) 1-x1 C x1 Gradient layer; the binary alloy layer includes a pure binary alloy layer close to the workpiece and a gradient binary alloy layer away from the workpiece, the pure binary alloy layer is a TiAl layer or a CrAl layer, and the gradient binary alloy layer is (TiAl) 1-x2 N x2 Gradient layer or (CrAl) 1-x2 (CN) x2 Gradient layer; the ternary nitride layer is (TiAl) 1-X3 N X3 Layer or (CrAl) 1-X3 N X3 layer, the quaternary nitride layer is (CrAlSi) 1-X3 N X3Layer or (TiAlSi) 1-X3 N X3 layer.

[0006] As a preferred embodiment, the FeMnCrCo layer and (FeMnCrCo) 1-x1 C x1 The alloy elements FeMnCrCo in the gradient layer include 40at% Fe, 40at% Mn, 10at% Cr and 10at% Co, of which 0 <X1≤0.05。

[0007] As a preferred embodiment, the TiAl layer and (TiAl) 1-x2 N x2 The alloy elements TiAl in the gradient layer include 60at%-70at% Ti and 30at%-40at% Al; the CrAl layer and (CrAl) 1-x2 (CN) x2 The alloying elements CrAl in the gradient layer include 50at% Cr and 50at% Al, of which 0 <X2≤0.5。

[0008] As a preferred embodiment, the (TiAl) 1-X3 N X3 The alloy elements TiAl in the layer include 35at% Ti and 65at% Al, and the (CrAlSi) 1-X3 N X3 The alloy elements CrAlSi in the layer include 32at% Cr, 60at% Al and 8at% Si. 1-X3 N X3 The alloy elements TiAlSi in the layer include 30at% Ti, 61at% Al and 9at% Si, of which 0 <X3≤0.5。

[0009] As a preferred embodiment, the thickness of the high entropy alloy layer is 251nm-470nm, the thickness of the pure binary alloy layer is 200nm-300nm, the thickness of the gradient binary alloy layer is 250nm-300nm, and the thickness of the ternary nitride layer or the quaternary nitride layer is 1μm-10μm.

[0010] As a preferred embodiment, the FeMnCrCo layer, (FeMnCrCo) and 1-x1 C x1 Gradient layer, TiAl layer, (TiAl) 1-x2 N x2 Gradient layer and (TiAl) 1-X3 N X3 layer.

[0011] As a preferred solution, the FeMnCrCo layer, the CrAl layer, and the (CrAl) layer are sequentially applied to the workpiece. 1-x2 (CN) x2 Gradient layer and (CrAlSi) 1-X3 N X3 layer.

[0012] As a preferred solution, it includes (FeMnCrCo) applied to the workpiece in sequence 1-x1 C x1 Gradient layer, TiAl layer, (TiAl) 1-x2 N x2 Gradient layer and (TiAlSi) 1-X3 N X3 layer.

[0013] In order to solve the above technical problems, the second object of the present invention is to provide a method for preparing an impact-resistant high-hardness coating, comprising the following steps:

[0014] 1) The workpiece is activated by ion etching;

[0015] 2) Preparation of high entropy alloy layer by magnetron sputtering;

[0016] 3) preparing a pure binary alloy layer and a gradient binary alloy layer in sequence by cathode arc;

[0017] 4) Preparation of ternary or quaternary nitride layers by cathode arc.

[0018] As a preferred solution, in step 1), the specific steps are to introduce argon gas through the ion source to maintain the pressure of the vacuum chamber at 0.1 Pa, turn on the ion source to bombard the cleaning test piece and apply a workpiece bias of -200V.

[0019] As a preferred solution, in step 2) the FeMnCrCo layer and / or (FeMnCrCo) 1-x1 C x1 Gradient layer preparation; The specific steps of FeMnCrCo layer preparation are: using FeMnCrCo target, using a unipolar pulsed DC power supply, bias voltage -100V to -150V, frequency 40kHz, duty cycle 80% magnetron sputtering method to prepare FeMnCrCo layer; (FeMnCrCo) 1-x1 C x1 The specific steps of preparing the gradient layer are as follows: using unipolar pulsed DC magnetron sputtering FeMnCrCo target, bias voltage -100V to -150V, frequency 40kHz, duty cycle 80%, vacuum chamber pressure reaching 0.1Pa, adjusting the methane gas flow rate to increase linearly from 0sccm to 40sccm within 40 minutes, and obtaining (FeMnCrCo) 1-x1 C x1 Gradient layer.

[0020] As a preferred solution, in step 3), the specific steps are: turn off the magnetron power supply and methane gas, maintain the vacuum chamber pressure at 0.3Pa, start a DC arc CrAl target or TiAl target, the arc target current is 90A-120A, the bias voltage is -120V~-150V, deposit a pure binary alloy layer, then start and linearly gradient adjust the nitrogen and methane flow rates, and increase the vacuum chamber pressure to 2Pa within 12min-20min to obtain a gradient binary alloy layer.

[0021] As a preferred scheme, in step 4), the specific steps are: continue to start the DC arc CrAl target or TiAl target, adjust the nitrogen flow rate and / or methane gas flow rate to increase the vacuum chamber pressure to 3Pa-6Pa, start the cathode arc pure Al target or AlSi target, open the shielding door, maintain the workpiece bias voltage of -100 to -150V, and obtain a ternary or quaternary nitride layer.

[0022] In order to solve the above technical problems, the third object of the present invention provides the application of the above-mentioned impact-resistant high-hardness coating in the field of cutting tools or sports equipment.

[0023] Compared with the prior art, the embodiments of the present invention have the following beneficial effects:

[0024] 1. The coating of the present application utilizes the high strength and high toughness of the interface of the top ternary or quaternary nitride layer to effectively inhibit the initiation of cracks; at the same time, the characteristic of vapor deposition that is convenient for composition modulation is utilized, and a pure metal high entropy alloy layer and a carbon gradient high entropy alloy layer are composited to obtain an interface bottom layer, which has high adhesion and high toughness, as well as high strength and high hardness, and inhibits the initiation of cracks at the membrane-base interface during high-speed impact / strike; in addition, a binary alloy buffer layer is designed between the top and bottom layers to coordinate the interlayer differences in deformation caused by instantaneous high loads. The buffer layer can reconcile the deformation caused by high-speed and high-load impacts, and can form a good composition and mechanical compatibility with the top hard coating. Through the interactive overlapping composite of the hard layer and the soft layer, a hard-soft effect is achieved, which can effectively inhibit the expansion of cracks, so that the overall coating achieves high toughness, high strength, high hardness, and anti-peeling properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 - is a schematic structural diagram of an impact-resistant high-hardness coating in Example 1 of the present invention;

[0026] Figure 2 - is a schematic structural diagram of an impact-resistant high-hardness coating in Example 2 of the present invention;

[0027] Figure 3 - is a schematic structural diagram of an impact-resistant high-hardness coating in Example 3 of the present invention;

[0028] Figure 4- is a schematic structural diagram of an impact-resistant high-hardness coating in Comparative Example 1 of the present invention;

[0029] Among them, the figure numbers of the drawings in the specification are as follows: 1. workpiece; 2. high entropy alloy layer; 2.1. pure metal high entropy alloy layer; 2.2. carbon gradient high entropy alloy layer; 3. binary alloy layer; 3.1. pure binary alloy layer; 3.2. gradient binary alloy layer; 4. ternary nitride layer; 5. quaternary nitride layer. DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Description of ingredients in this application:

[0032] 1) Multi-element alloy: directly use the element symbol, such as TiAl alloy;

[0033] 2) Specific alloy: Write down the atomic percentage of the elemental composition, such as the abbreviated Ti40Al60 alloy, which means it contains 40at% Ti and 60at% Al;

[0034] 3) Specific compounds: as abbreviated (Ti 33 Al 67 ) 0.5 N 0.5 , where the total alloy metal elements account for 50%, non-metallic N accounts for 50%, among which Ti 33 Al 67 Comprising 33at% Ti and 67at% Al.

[0035] The present application provides an impact-resistant high-hardness coating, which can be applied to the fields of cutting tools or sports equipment, including a high-entropy alloy layer 2, a binary alloy layer 3, and a ternary nitride layer 4 or a quaternary nitride layer 5 sequentially coated on the surface of a workpiece 1, the workpiece is a conductive metal, the high-entropy alloy layer 2 includes a pure metal high-entropy alloy layer 21 and / or a carbon gradient high-entropy alloy layer 22, the pure metal high-entropy alloy layer 21 is a FeMnCrCo layer, and the carbon gradient high-entropy alloy layer 22 is (FeMnCrCo) 1-x1 C x1 The binary alloy layer 3 includes a pure binary alloy layer 31 and a gradient binary alloy layer 32 which are sequentially applied. The pure binary alloy layer 31 may be a TiAl layer or a CrAl layer, and the gradient binary alloy layer 32 may be (TiAl) 1-x2 N x2Gradient layer or (CrAl) 1-x2 (CN) x2 Gradient layer; ternary nitride layer 4 can be (TiAl) 1-X3 N X3 Layer or (CrAl) 1-X3 N X3 layer, the quaternary nitride layer 5 may be (CrAlSi) 1-X3 N X3 Layer or (TiAlSi) 1-X3 N X3 The layer specifically comprises the following preparation steps:

[0036] 1) Cleaning and drying of workpiece surface;

[0037] 2) The workpiece is activated by ion etching;

[0038] 3) preparing a high entropy alloy layer 2 by magnetron sputtering;

[0039] 4) The cathode arc sequentially prepares a pure binary alloy layer 31 and a gradient binary alloy layer 32;

[0040] 5) Cathodic arc is used to prepare a ternary nitride layer 4 or a quaternary nitride layer 5 .

[0041] In one embodiment, the FeMnCrCo layer and the (FeMnCrCo) 1-x1 C x1 The gradient layers are all sputtered by FeMnCrCo target, and the FeMnCrCo target includes the following components: 40at% Fe, 40at% Mn, 10at% Cr, 10at% Co. The FeMnCrCo layer is abbreviated as: Fe40Mn40Cr10Co10 layer, (FeMnCrCo) 1-x1 C x1 The gradient layer is abbreviated as: (Fe 40 Mn 40 Cr 10 Co 10 ) 1-x1 C x1 .

[0042] In one embodiment, (FeMnCrCo) 1-x1 C x1 Gradient layer 0 <X1≤0.05。

[0043] In one embodiment, the TiAl layer and the (TiAl) 1-x2 N x2The gradient layers are all sputtered by TiAl target, and the TiAl target includes the following components: 60at%-70at% Ti and 30at%-40at% Al. The TiAl layer is abbreviated as: Ti60Al40 layer or Ti70Al30 layer, (TiAl) 1-x2 N x2 The gradient layer is abbreviated as: (Ti 60 Al 40 ) 1-x2 N x2 Gradient layer or (Ti 70 Al 30 ) 1-x2 N x2 Gradient layer.

[0044] In one embodiment, the CrAl layer and (CrAl) 1-x2 (CN) x2 The gradient layers are all sputtered by CrAl target, which includes the following components: 50at% Cr and 50at% Al. The CrAl layer is abbreviated as: Cr50Al50 layer, (CrAl) 1-x2 (CN) x2 The gradient layer is abbreviated as: (Cr 50 Al 50 ) 1-x2 (CN) x2 Gradient layer.

[0045] In one embodiment, (TiAl) 1-x2 N x2 Gradient layer and (CrAl) 1-x2 (CN) x2 Gradient layer 0 <X2≤0.5。

[0046] In one embodiment, (TiAl) 1-X3 N X3 The alloying elements TiAl in the layer include the following composition: 35at%Ti, 65at%Al, abbreviated as: (Ti 35 Al 65 ) 1-X3 N X3 Layer, (CrAlSi) 1-X3 N X3 The alloying elements CrAlSi in the layer include the following composition: 32at%Cr, 60at%Al and 8at%Si, abbreviated as: (Cr 32 Al 60 Si8) 1-X3 N X3 , (TiAlSi) 1-X3 N X3The alloying elements TiAlSi in the layer include the following composition: 30at% Ti, 61at% Al and 9at% Si, abbreviated as: (Ti 30 Al 61 Si9) 1-X3 N X3 .

[0047] In one embodiment, (TiAlSi) 1-X3 N X3 Layer and (CrAlSi) 1-X3 N X3 Layer 0 <X3≤0.5。

[0048] In one embodiment, the thickness of the pure metal high entropy alloy layer 21 is 0 nm-500 nm, and the thickness of the carbon gradient alloy layer 22 is 0 nm-251 nm.

[0049] In one embodiment, the thickness of the pure binary alloy layer 31 is 200 nm-300 nm, and the thickness of the gradient binary alloy layer 32 is 250 nm-300 nm.

[0050] In one embodiment, the thickness of the ternary nitride layer 4 or the quaternary nitride layer 5 is 1 μm-10 μm.

[0051] In one embodiment, step 1) specifically involves cleaning and drying the surface of the workpiece, placing it in a vacuum chamber, and starting the workpiece bracket to rotate.

[0052] In one embodiment, step 2) is specifically to introduce argon gas through the ion source to maintain the pressure of the vacuum chamber at 0.1Pa, turn on the ion source to bombard the cleaning test piece and apply a workpiece bias of -200V, and heat the sample to 400℃-600℃ while etching and activating, and maintain this temperature until the coating deposition is completed.

[0053] The present application utilizes argon plasma to etch, clean and activate the surface of a workpiece substrate to which a negative pulse bias voltage is applied, thereby improving the interface state and enhancing the bonding force between the coating and the workpiece substrate.

[0054] In one embodiment, step 3) specifically includes a FeMnCrCo layer and / or (FeMnCrCo) 1-x C x Gradient layer preparation; The specific steps of FeMnCrCo layer preparation are: using FeMnCrCo magnetron target, using unipolar pulsed DC power supply, bias voltage -100V ~ -150V, frequency 40kHz, duty cycle 80% magnetron sputtering method to prepare FeMnCrCo layer; (FeMnCrCo) 1-x C xThe specific steps of preparing the gradient layer are as follows: using unipolar pulsed DC magnetron sputtering FeMnCrCo high entropy alloy target, bias voltage -100V to -150V, frequency 40kHz, duty cycle 80%, vacuum chamber pressure reaching 0.1Pa, adjusting the methane gas flow rate to increase linearly from 0sccm to 40sccm within 40 minutes, and obtaining (FeMnCrCo) 1-x C x Gradient layer.

[0055] In one embodiment, step 4) is specifically to turn off the magnetron power supply and methane gas, maintain the vacuum chamber pressure at 0.3Pa, start a DC arc CrAl target or TiAl target, the arc target current is 90A-120A, the bias voltage is -120V~-150V, deposit a pure alloy layer, and then start and linearly gradient adjust the nitrogen and methane flow rates, and increase the vacuum chamber pressure to 2Pa within 12min-20min to obtain a gradient alloy layer.

[0056] In one embodiment, step 5) specifically includes the preparation of a ternary nitride layer 4 or a quaternary nitride layer 5; the specific steps of preparing the ternary nitride layer 4 are: continue to operate the DC arc CrAl target or TiAl target, adjust the nitrogen flow rate to increase the vacuum chamber pressure to 3Pa, start the cathode arc pure Al target, open the shielding door, maintain the workpiece bias voltage of -100 to -150V, and obtain the ternary nitride layer 4; the specific steps of preparing the quaternary nitride layer 5 are: continue to operate the DC arc CrAl target or TiAl target, turn off the methane gas, adjust the nitrogen flow rate to increase the vacuum chamber pressure to 6Pa, start the alloy cathode arc AlSi target, open the shielding door, bias the voltage of -100V to -150V, and prepare the quaternary nitride layer 5.

[0057] When the coating is subjected to strong impact or strike, the initiation and propagation of cracks are the essential problems that lead to coating peeling. During impact / strike, the maximum tensile stress or shear stress occurs in the sub-surface layer and the surface at a certain distance from the striking point, which is the interface for most hard coatings. Therefore, the high strength and high toughness of the interface of the ternary or quaternary nitride layer of the coating of the present application are the key to inhibiting crack initiation.

[0058] At the same time, the present application takes advantage of the characteristic of vapor deposition that it is easy to modulate the composition, and is designed to use a layer of pure metal high entropy alloy 21, a carbon gradient high entropy alloy layer 22, or a composite of the two to obtain an interface bottom layer with high adhesion and high toughness, as well as high strength and high hardness, to inhibit the initiation of cracks at the membrane-base interface during high-speed impact / strike.

[0059] In addition, in order to effectively inhibit crack propagation, the present application designs a binary alloy buffer layer between the top high-hardness ternary or quaternary nitride layers to coordinate the inter-layer deformation differences caused by instantaneous high loads. The buffer layer can reconcile the deformation caused by high-speed and high-load impact, and can form a good composition and mechanical compatibility with the top hard coating. Through the interactive overlapping and compounding of the hard layer and the soft layer, the effect of combining hardness and flexibility is achieved, which can effectively inhibit the propagation of cracks.

[0060] The following is an elaboration in conjunction with specific embodiments to demonstrate the practical effect of the present application solution.

[0061] Embodiment 1

[0062] An impact-resistant high-hardness coating, such as Figure 1 As shown, the high entropy alloy layer 2, the binary alloy layer 3 and the ternary nitride layer 4 are sequentially coated on the surface of the test piece workpiece 1, and the high entropy alloy layer 2 includes a Fe40Mn40Cr10Co10 layer with a thickness of 100nm and a (Fe40Mn40Cr10Co10 layer with a thickness of 245nm. 40 Mn 40 Cr 10 Co 10 ) 1-x1 C x1 Gradient layer, wherein X1 = 0.032, the binary alloy layer 3 comprises a Ti70Al30 layer with a thickness of 300 nm and a (Ti 70 Al 30 ) 0.5 N 0.5 Gradient layer, ternary nitride layer 4 is 1 μm thick (Ti 35 Al 65 ) 0.5 N 0.5 The layer specifically comprises the following preparation steps:

[0063] 1) A square 304 stainless steel alloy test piece with a size of 20x20x5mm was cleaned in a cleaning line. After the surface of the test piece was clean, it was dried with oil-free compressed air, mounted on a fixture and placed in the vacuum chamber of the HauzerFlexcoat 850 coating system, and the workpiece bracket was started to rotate;

[0064] 2) The back vacuum of the vacuum chamber is less than 5x10 -3 After 1.5 Pa, argon gas was introduced through the air inlet of the ion source to maintain the pressure of the vacuum chamber at 0.1 Pa. The ion source was turned on to bombard and clean the test piece and a workpiece bias voltage of -200 V was applied. During this period, the DC arc current was maintained at 30 A. The ion bombardment cleaning was turned off after 40 minutes. While etching and activating, the heating power supply was turned on to heat the sample to 400 ° C. This temperature was maintained until the coating deposition was completed.

[0065] 3) Start the unipolar pulsed DC magnetron sputtering of Fe40Mn40Cr10Co10 target, with a target power of 3.5kW, a bias voltage of -100V, a frequency of 40kHz, a duty cycle of 80%, and only argon gas is introduced into the vacuum chamber and the pressure is maintained at 0.1Pa. The Fe40Mn40Cr10Co10 layer is deposited for 10 minutes, and then the methane gas flow rate is adjusted to increase from 0sccm to 30sccm within 30 minutes. A 245nm gradient (Fe 40 Mn 40 Cr 10 Co 10 ) 1-x1 C x1 Gradient layer, the C content of this layer, namely X1, is 3.2% according to spectral analysis, wherein the Fe40Mn40Cr10Co10 target comprises the following components: 40at% Fe, 40at% Mn, 10at% Cr and 10at% Co.

[0066] 4) Turn off the magnetron power supply and methane gas, introduce argon gas to maintain the vacuum chamber pressure at 0.3Pa, start the DC arc Ti70Al30 target, the arc target current is 100A, the workpiece bias voltage is -150V, and the Ti70Al30 layer is deposited. Then the nitrogen flow rate is linearly adjusted to increase the vacuum chamber pressure to 2Pa within 15 minutes to prepare (Ti 70 Al 30 ) 0.5 N 0.5 Gradient layer, where X2 = 0.5, Ti70Al30 target includes the following composition: 70at% Ti and 30at% Al.

[0067] 5) Continue to operate the alloy cathode arc Ti70Al30 target, adjust the nitrogen flow rate to increase the vacuum chamber pressure to 3Pa, operate the pure Al cathode arc target, open the shielding door, maintain the workpiece bias voltage -150V, and prepare (Ti 35 Al 65 ) 0.5 N 0.5 After the coating is prepared, the workpiece is taken out after cooling down to below 150°C in the furnace. 35 Al 65 ) 0.5 N 0.5 Alloy element Ti in the layer 35 Al 65 The composition includes 35 at% Ti and 65 at% Al.

[0068] During the performance test, the surface hardness of the test piece coating was tested using an MVA401 microhardness tester with a load of 10g, and the result was 2989HV. The film-base bonding strength of the test piece coating was tested using an MFT-4000 scratch tester with an indenter diameter of 200μm, and the result reached 95N. The test piece was welded to a golf head and tested by swinging with a force of 70kg in a sand pit on a practice course. After 300 hits, there were only a few cuts on the surface, and no coating peeling was observed.

[0069] Embodiment 2

[0070] An impact-resistant high-hardness coating, such as Figure 2 As shown, it includes a high entropy alloy layer 2, a binary alloy layer 3 and a quaternary nitride layer 5 which are sequentially coated on the surface of the test piece workpiece 1. The high entropy alloy layer 2 is a Fe40Mn40Cr10Co10 layer with a thickness of 470nm, and the binary alloy layer 3 includes a Cr50Al50 layer with a thickness of 200nm and a (Cr 50 Al 50 ) 0.5 (CN) 0.5 Gradient layer, quaternary nitride layer 5 is 3 μm thick (Cr 32 Al 60 Si8) 0.5 N 0.5 The layer specifically comprises the following preparation steps:

[0071] 1) A square Ti6Al4V alloy specimen with a size of 20x20x5mm was cleaned in a cleaning line to make the surface clean, then dried with oil-free compressed air, mounted on a fixture and placed in the vacuum chamber of the HauzerFlexcoat 850 coating system, and the workpiece bracket was started to rotate;

[0072] 2) The back vacuum of the vacuum chamber is less than 5x10 -3 After 1.5 Pa, argon gas was introduced through the air inlet of the ion source to maintain the pressure of the vacuum chamber at 0.1 Pa. The ion source was turned on to bombard and clean the test piece and a workpiece bias voltage of -200 V was applied. During this period, the DC arc current was maintained at 30 A. The ion bombardment cleaning was turned off after 40 minutes. While etching and activating, the heating power supply was turned on to heat the sample to 600 ° C. This temperature was maintained until the coating deposition was completed.

[0073] 3) Start unipolar pulsed DC magnetron sputtering of Fe40Mn40Cr10Co10 target with target power of 3.5kW, bias voltage of -150V, frequency of 40kHz, duty cycle of 80%, introduce argon into the vacuum chamber and maintain the pressure at 0.1Pa, and deposit for 45 minutes to obtain a 470nm thick Fe40Mn40Cr10Co10 layer, wherein the Fe40Mn40Cr10Co10 target includes the following components: 40at% Fe, 40at% Mn, 10at% Cr and 10at% Co.

[0074] 4) Turn off the magnetron power supply, introduce argon to maintain the vacuum chamber pressure at 0.3Pa, start the DC arc Cr50Al50 target, the arc target current is 120A, the workpiece bias voltage is -120V, and a 200nm thick Cr50Al50 layer is deposited; then the flow rate of nitrogen + methane (volume ratio 1:1) is linearly adjusted to increase the vacuum chamber pressure to 2Pa within 20 minutes, and a 300nm thick gradient layer (Cr 50 Al 50 ) 0.5 (CN) 0.5 , where the Cr50Al50 target includes the following composition: 50at% Cr and 50at% Al.

[0075] Step 5: Continue to start the Cr50Al50 alloy cathode arc target, turn off the methane gas, adjust the nitrogen flow rate to increase the vacuum chamber pressure to 6Pa, start the Al80Si20 alloy cathode arc target, open the shielding door, maintain the workpiece bias voltage -120V, and prepare a 3 μm thick (Cr 32 Al 60 Si8) 0.5 N 0.5 After the coating is prepared, the workpiece is taken out after cooling down to below 150°C in the furnace. The Al80Si20 target includes the following components: 80at% Al and 20at% Si, (Cr 32 Al 60 Si8) 0.5 N 0.5 Alloying element Cr in the layer 32 Al 60 Si8 includes the following composition: 32at% Cr, 60at% Al and 8at% Si.

[0076] During the performance test, the surface hardness of the test piece coating was tested by using an MVA401 microhardness tester with a load of 10g, and the result was 3348HV. The film-base bonding strength of the test piece coating was tested by using an MFT-4000 scratch tester with a head diameter of 200μm, and the result was greater than 100N. The test piece was welded to a golf head and tested by swinging with a force of 70kg in a sand pit on a practice course. After 400 hits, there were only a few cuts on the surface, and no coating peeling was observed.

[0077] Embodiment 3

[0078] An impact-resistant high-hardness coating, such as Figure 3 As shown, the high entropy alloy layer 2, the binary alloy layer 3 and the quaternary nitride layer 5 are sequentially coated on the surface of the test piece workpiece 1, and the high entropy alloy layer 2 is (Fe 40 Mn 40 Cr 10 Co 10) 1-x1 C x1 Gradient layer, where X1 = 0.041, the binary alloy layer 3 includes a Ti60Al40 layer with a thickness of 250nm and a (Ti 60 Al 40 ) 0.5 N 0.5 Gradient layer, quaternary nitride layer 5 is 10 μm thick (Ti 30 Al 61 Si9) 0.5 N 0.5 The layer specifically comprises the following preparation steps:

[0079] 1) A square PH-17 metal test piece with a size of 20x20x5mm and electroplated with Ni-Cr was cleaned in a cleaning line. After the surface was cleaned, it was dried with oil-free compressed air, hung on a fixture and placed in the vacuum chamber of the HauzerFlexcoat 850 coating system, and the workpiece bracket was started to rotate;

[0080] 2) The back vacuum of the vacuum chamber is less than 5x10 -3 After 0.05 Pa, argon gas was introduced through the gas inlet of the ion source to maintain the pressure of the vacuum chamber at 0.1 Pa. The ion source was turned on to bombard and clean the test piece and a workpiece bias voltage of -200 V was applied. During this period, the DC arc current was maintained at 30 A. The ion bombardment cleaning was turned off after 40 minutes. While etching and activating, the heating power supply was turned on to heat the sample to 450 ° C. This temperature was maintained until the coating deposition was completed.

[0081] 3) Start the unipolar pulsed DC magnetron sputtering of Fe40Mn40Cr10Co10 target, target power 3.5kW, bias voltage -120V, frequency 40kHz, duty cycle 80%, introduce argon gas to make the vacuum chamber pressure reach 0.1Pa, then immediately adjust the methane gas flow rate to increase linearly from 0sccm to 40sccm within 40 minutes, and coat 251nm thick (Fe 40 Mn 40 Cr 10 Co 10 ) 1-x1 C x1 The Fe40Mn40Cr10Co10 target comprises the following components: 40at% Fe, 40at% Mn, 10at% Cr and 10at% Co.

[0082] 4) Turn off the magnetron power supply and methane gas, introduce argon gas to maintain the vacuum chamber pressure at 0.3Pa, start the DC arc Ti60Al40 target, the arc target current is 90A, the workpiece bias voltage is -120V, and a 250nm thick T60Al40 layer is deposited; then the nitrogen flow rate is linearly adjusted to increase the vacuum chamber pressure to 2Pa within 12 minutes to prepare a 250nm thick (Ti 60 Al 40 ) 0.5 N 0.5 layer, wherein the Ti60Al40 target comprises the following composition: 60at% Ti and 40at% Al.

[0083] 5) Continue to operate the Ti60Al40 alloy cathode arc target, adjust the nitrogen flow rate to increase the vacuum chamber pressure to 2Pa, operate the Al80Si20 aluminum alloy cathode arc target, open the shielding door, maintain the workpiece bias voltage at -120V, and prepare a 10 μm thick (Ti 30 Al 61 Si9) 0.5 N 0.5 After the coating is prepared, the workpiece is taken out after cooling down to below 150°C in the furnace. The Al80Si20 target includes the following components: 80at% Al and 20at% Si, (Ti 30 Al 61 Si9) 0.5 N 0.5 Alloy element Ti in the layer 30 Al 61 Si9 includes the following composition: 30at% Ti, 61at% Al and 9at% Si.

[0084] During the performance test, the surface hardness of the test piece coating was tested by using an MVA401 microhardness tester with a load of 10g, and the result was 3217HV. The film-base bonding strength of the test piece coating was tested by using an MFT-4000 scratch tester with a head diameter of 200μm, and the result reached 98N. The test piece was welded to a golf head and tested by swinging with a force of 70kg in a sand pit on a practice course. After 400 swings, there were only a few cuts on the surface, and no coating peeling was observed.

[0085] Comparative Example 1

[0086] An impact-resistant high-hardness coating, such as Figure 4 As shown, the quaternary nitride layer 5 is coated and arranged on the surface of the test piece workpiece 1, and the quaternary nitride layer 5 is (Ti 30 Al 61 Si9) 0.5 N 0.5 The layer specifically comprises the following preparation steps:

[0087] 1) A square PH-17 metal test piece with a size of 20x20x5mm and electroplated with Ni-Cr was cleaned in a cleaning line. After the surface was cleaned, it was dried with oil-free compressed air, hung on a fixture and placed in the vacuum chamber of the HauzerFlexcoat 850 coating system, and the workpiece bracket was started to rotate;

[0088] 2) The back vacuum of the vacuum chamber is less than 5x10 -3 After 0.05 Pa, argon gas was introduced through the gas inlet of the ion source to maintain the pressure of the vacuum chamber at 0.1 Pa. The ion source was turned on to bombard and clean the test piece and apply a workpiece bias of -200 V. During this period, the DC arc current was maintained at 30 A. The ion bombardment cleaning was turned off after 40 minutes. While etching and activating, the heating power supply was turned on to heat the sample to 450 ° C. This temperature was maintained until the coating deposition was completed.

[0089] 3) Ar was introduced to make the vacuum chamber pressure reach 0.3Pa, then the Ti60Al40 alloy cathode arc target and Al80Si20 aluminum alloy cathode arc target were started, the nitrogen flow rate was adjusted to increase the vacuum chamber pressure to 2Pa, the workpiece bias voltage was maintained at 120V, and a 10 μm thick (Ti 30 Al 61 Si9) 0.5 N 0.5 After the coating preparation is completed, the workpiece is taken out after cooling down below 150°C in the furnace. The Ti60Al40 target includes the following components: 60at% Ti and 40at% Al, and the Al80Si20 target includes the following components: 80at% Al and 20at% Si. 30 Al 61 Si9) 0.5 N 0.5 Alloy element Ti in the layer 30 Al 61 Si9 includes the following composition: 30at% Ti, 61at% Al and 9at% Si.

[0090] In the performance test, the surface hardness of the test piece coating was tested to be 3198HV using an MVA401 microhardness tester with a load of 10g. The film-base bonding strength of the test piece coating was tested to be 30N using an MFT-4000 scratch tester with an indenter diameter of 200μm. The test piece was welded to a golf head and tested by swinging with a force of 70kg in a sand pit on a practice course. After 20 hits, large pieces of the surface coating peeled off.

[0091] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. It is particularly pointed out that for those skilled in the art, any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of protection of the present invention.

Claims

1. An impact-resistant high-hardness coating, characterized in that: The invention comprises a high entropy alloy layer (2), a binary alloy layer (3) and a ternary nitride layer (4) or a quaternary nitride layer (5) which are sequentially applied to a workpiece (1), wherein the high entropy alloy layer (2) comprises a FeMnCrCo layer and / or (FeMnCrCo) 1-x1 C x1 gradient layer; the binary alloy layer (3) comprises a pure binary alloy layer (31) and a gradient binary alloy layer (32) applied in sequence, the pure binary alloy layer (31) being a TiAl layer, and the gradient binary alloy layer (32) being a (TiAl) 1-x2 N x2 Gradient layer; the ternary nitride layer (4) is (TiAl) 1-X3 N X3 layer, the quaternary nitride layer (5) is (TiAlSi) 1-X3 N X3 layer; The FeMnCrCo layer and (FeMnCrCo) 1-x1 C x1 The alloy elements FeMnCrCo in the gradient layer include 40at% Fe, 40at% Mn, 10at% Cr and 10at% Co, of which 0 <X1≤0.05; The TiAl layer and (TiAl) 1-x2 N x2 The alloy elements TiAl in the gradient layer include 60at%-70at% Ti and 30at%-40at% Al, of which 0 <X2≤0.5; The (TiAl) 1-X3 N X3 The alloying elements TiAl in the layer include 35at% Ti and 65at% Al, of which 0 <X3≤0.5; (TiAlSi) 1-X3 N X3 The alloy elements TiAlSi in the layer include 30at% Ti, 61at% Al and 9at% Si, of which 0 <X3≤0.5。 2. An impact-resistant high-hardness coating, characterized in that: The invention comprises a high entropy alloy layer (2), a binary alloy layer (3) and a ternary nitride layer (4) or a quaternary nitride layer (5) which are sequentially applied to a workpiece (1), wherein the high entropy alloy layer (2) comprises a FeMnCrCo layer and / or (FeMnCrCo) 1-x1 C x1 The binary alloy layer (3) comprises a pure binary alloy layer (31) and a gradient binary alloy layer (32) which are applied in sequence, wherein the pure binary alloy layer (31) is a CrAl layer, and the gradient binary alloy layer (32) is (CrAl) 1-x2 (CN) x2 Gradient layer; the ternary nitride layer (4) is (CrAl) 1-X3 N X3 layer, the quaternary nitride layer (5) is (CrAlSi) 1-X3 N X3 layer; The FeMnCrCo layer and (FeMnCrCo) 1-x1 C x1 The alloy elements FeMnCrCo in the gradient layer include 40at% Fe, 40at% Mn, 10at% Cr and 10at% Co, of which 0 <X1≤0.05; The CrAl layer and (CrAl) 1-x2 (CN) x2 The alloying elements CrAl in the gradient layer include 50at% Cr and 50at% Al, of which 0 <X2≤0.5; (CrAlSi) 1-X3 N X3 The alloy elements CrAlSi in the layer include 32at% Cr, 60at% Al and 8at% Si, of which 0 <X3≤0.5。 3. An impact-resistant high-hardness coating as claimed in claim 1 or 2, characterized in that: The thickness of the high entropy alloy layer (2) is 251nm-470nm, the thickness of the pure binary alloy layer (31) is 200nm-300nm, the thickness of the gradient binary alloy layer (32) is 250nm-300nm, and the thickness of the ternary nitride layer (4) or the quaternary nitride layer (5) is 1μm-10μm.

4. A method for preparing an impact-resistant high-hardness coating, characterized in that: The method for preparing an impact-resistant high-hardness coating as claimed in any one of claims 1 to 3 comprises the following steps: 1) The workpiece is activated by ion etching; 2) Preparation of high entropy alloy layer by magnetron sputtering; 3) preparing a pure binary alloy layer and a gradient binary alloy layer in sequence by cathode arc; 4) Preparation of ternary or quaternary nitride layers by cathode arc; In step 1), the specific steps are to introduce argon gas through the ion source to maintain the pressure of the vacuum chamber at 0.1 Pa, turn on the ion source to bombard the cleaning test piece and apply a workpiece bias voltage of -200V.

5. The method for preparing an impact-resistant high-hardness coating according to claim 4, characterized in that: In step 2) including a FeMnCrCo layer and / or (FeMnCrCo) 1-x C x Gradient layer preparation; The specific steps of preparing the FeMnCrCo layer are as follows: using a FeMnCrCo target, a unipolar pulsed DC power supply, a bias voltage of -100V to -150V, a frequency of 40kHz, and a duty cycle of 80% to prepare the FeMnCrCo layer by magnetron sputtering; (FeMnCrCo) 1-x C x The specific steps of preparing the gradient layer are as follows: using unipolar pulsed DC magnetron sputtering FeMnCrCo target, bias voltage -100V to -150V, frequency 40kHz, duty cycle 80%, vacuum chamber pressure reaching 0.1Pa, adjusting the methane gas flow rate to increase linearly from 0sccm to 40sccm within 40 minutes, and obtaining (FeMnCrCo) 1-x C x Gradient layer.

6. The method for preparing an impact-resistant high-hardness coating according to claim 5, characterized in that: In step 3), the specific steps are: turn off the magnetron power supply and methane gas, maintain the vacuum chamber pressure at 0.3Pa, start a DC arc CrAl target or TiAl target, arc target current 90A-120A, bias -120V~-150V, deposit a pure binary alloy layer, then turn on and linearly gradient adjust the nitrogen and methane flow rates, and increase the vacuum chamber pressure to 2Pa within 12min-20min to obtain a gradient binary alloy layer.

7. The method for preparing an impact-resistant high-hardness coating according to claim 6, characterized in that: In step 4), the specific steps are: continue to start the DC arc CrAl target or TiAl target, adjust the nitrogen flow rate to increase the vacuum chamber pressure to 3Pa-6Pa, start the cathode arc pure Al target or AlSi target, open the shielding door, maintain the workpiece bias voltage of -100 to -150V, and obtain a ternary or quaternary nitride layer.

8. Use of the impact-resistant high-hardness coating according to any one of claims 1 to 3 in the field of cutting tools or sports equipment.